ANALISIS SALURAN DISTRIBUSI WISATAWAN MANCANEGARA DI PULAU BALI - Bhirawa Manggala; Supriono Supriono (Fakultas Ilmu Administrasi Universitas Brawijaya, 2018)
Bali is the most promotable island that promoted by travel agents, the Government and Society. This makes big accumulation of foreign tourists traveling on Bali island. Based on the above problems, the researchers in the study are interested to lift the title